Process simulation using WITNESS - Al-Aomar, Raid; Ulgen, Onur M., 1949-; Williams, Ed, 1944- (Hoboken, New Jersey : John Wiley & Sons, Incorporated, 2015)
"The first book to cover simulation using the popular software WITNESS, Process Simulation Using WITNESS helps professionals understand the theory behind simulation in a simple and practical manner while learning how to build simulation models with the software. This book outlines the role of simulation in contemporary initiatives for lean systems design and operations as well as Six Sigma applications. Emphasizing real-world applications of simulation modeling in both services and manufacturing sectors, the book is suitable for a broad audience, including system, simulation, material handling, layout, and operations engineers"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: WITNESS (Computer file); Operations research -- Data processing; Stochastic processes -- Computer simulation; Industrial engineering -- Graphic methods; Electronic books